Evaluasi Manfaat dan Dampak Pelaksanaan Kebijakan Sistem Zonasi Penerimaan Peserta Didik di Kecamatan Masamba Kabupaten Luwu Utara - Rusdin Said; Alimuddin Ramli; Sri Wahyuti (Departement of Mathematics Education, 2023)
The purpose of this study was to evaluate the benefits and impacts on the community (parents, family) and the school for the implementation of the zoning system policy for student acceptance in Masamba District, North Luwu Regency. The type of research used in this research is the mix method, namely a combination of qualitative and quantitative research methods using school data in Masamba District, North Luwu Regency, which totals 23 schools at the Kindergarten/equivalent level of education, 27 elementary/equivalent schools, 27 junior high schools/equivalent 12 schools, high school / equivalent 7 schools. The data collection techniques used were documentation studies, observations, interviews and questionnaires with data analysis techniques using the percentage method which then combined with Miles and Hubberman's theory, namely interactive analysis. The results showed that related to the zoning system policy for both the school and the community in this case students and parents had an impact on increasing knowledge, profits, making it easier for children/family members to be accepted at the nearest school, getting closer to school distances, reducing the burden of transportation costs, reducing the risk of being late to school due to traffic jams.